Digital humanities and the emerging framework for digital curation. Issue 2 (2nd October 2017) - Sabharwal, Arjun
ABSTRACT: Digital humanities (DH) represents an emerging framework for digital curation. This study focuses on the evolving relationship of the DH (including history) to digital curation and archives and describes the models of collaboration in the digital environment. A conceptual framework is presented, followed by discussions of scarcity and abundance, archival frameworks, models of collaboration, and a review of selected DH projects. Despite the semantic disagreements over the term archives, researchers and curators should consider each other's perspectives for continued collaboration.